2016
DOI: 10.1051/0004-6361/201628599
|View full text |Cite
|
Sign up to set email alerts
|

Flux-tube geometry and solar wind speed during an activity cycle

Abstract: Context. The solar wind speed at 1 AU shows cyclic variations in latitude and in time which reflect the evolution of the global background magnetic field during the activity cycle. It is commonly accepted that the terminal (asymptotic) wind speed in a given magnetic flux-tube is generally anti-correlated with its total expansion ratio, which motivated the definition of widely used semiempirical scaling laws relating one to the other. In practice, such scaling laws require ad hoc corrections (especially for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 40 publications
4
32
0
Order By: Relevance
“…These observations agree with the idea that both the fast and slow Alfvénic solar wind were produced on open field lines rooted in coronal holes, but with varying magnetic field geometries in the lower corona. In particular, the amount the magnetic field expands in the low corona (up to 2.5r ), the footpoint magnetic field strength, and the magnetic field inclination at the solar surface are all thought to be important in shaping the properties of coronal hole wind (Suess et al 1984;Wang & Sheeley 1990;Bravo & Stewart 1997;Suzuki 2006;Pinto et al 2016;Réville & Brun 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These observations agree with the idea that both the fast and slow Alfvénic solar wind were produced on open field lines rooted in coronal holes, but with varying magnetic field geometries in the lower corona. In particular, the amount the magnetic field expands in the low corona (up to 2.5r ), the footpoint magnetic field strength, and the magnetic field inclination at the solar surface are all thought to be important in shaping the properties of coronal hole wind (Suess et al 1984;Wang & Sheeley 1990;Bravo & Stewart 1997;Suzuki 2006;Pinto et al 2016;Réville & Brun 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This value is actually found to change during the solar cycle and for various stellar parameters (Lee et al 2011;Réville et al 2015b). It is also shown that Potential field source surface extrapolation of the coronal field overestimates the expansion factor ( f = A1 A0 r 0 r 1 2 = B0 B1 r 0 r 1 2 ; with A0, A1 the flux tube surface area at the surface and far in the wind, B0, B1 the magnetic field at the same locations and r 0, r 1 the surface and distant radius) which is one of the key ingredients for determining the stellar wind terminal velocity, see, e.g., Wang and Sheeley (1990), NOAA's WSA-Enlil model (Arge and Pizzo 2000;Mays et al 2015) and Pinto et al (2016). More accurate solar wind models have also been computed over an 11-year cycle, showing that the Alfvén radius and torque exerted by the solar wind changes by a factor of 3 between the minimum and maximum phases of the activity cycle (Pinto et al 2011(Pinto et al , 2016Réville et al 2016).…”
Section: Magnetic Effects On Coronal Activity and Windsmentioning
confidence: 99%
“…The reason slower speeds are not observable at the leading edge of high speed streams is because by 0.3 AU they have already been accelerated by the faster wind to form a co-rotating interaction region (Burlaga 1974;Pizzo 1991;McGregor et al 2011;Richardson 2018). Note that we have chosen to distinguish between the edges and the core of coronal holes; at the edge of coronal holes the magnetic field lines typically undergo large separations as a function of height in the corona, which has the effect of reducing both the wind speed (Levine et al 1977;Wang & Sheeley 1991;Cranmer et al 2007;Pinto et al 2016) and charge state ratios (Wang et al 2009). In the next two sections further evidence is used to predict which one of our three categories coronal hole edge wind is part of.…”
Section: Known Properties Of Coronal Hole Windmentioning
confidence: 99%